Vertical distribution of soil seed bank and the ecological importance of deeply buried seeds in alkaline grasslands - Tóth Ágnes; Deák Balázs; Tóth Katalin; Kiss Réka; Lukács Katalin; Rádai Zoltán; Godó Laura; Borza Sándor; Kelemen András; Miglécz Tamás; Bátori Zoltán; Novák Tibor József; et al. (2022)
Background: Soil seed banks play a central role in vegetation dynamics and may be an important source of ecological restoration. However, the vast majority of seed bank studies examined only the uppermost soil layers (0-10 cm); hence, our knowledge on the depth distribution of seed bank and the ecological significance of deeply buried seeds is limited. The aim of our study was to examine the fine-scale vertical distribution of soil seed bank to a depth of 80 cm, which is one of the largest studied depth gradients so far. Our model systems were alkaline grasslands in East-Hungary, characterised by harsh environmental conditions, due to Solonetz soil reference group with Vertic horizon. We asked the following questions: (1) How do the seedling density and species richness of soil seed bank change along a vertical gradient and to what depth can germinable seeds be detected? (2) What is the relationship between the depth distribution of the germinable seeds and the species traits? Methods: In each of the five study sites, four soil cores (4 cm diameter) of 80 cm depth were collected with an auger for soil seed bank analysis. Each sample was divided into sixteen 5-cm segments by depth (320 segments in total). Samples were concentrated by washing over sieves and then germinated in an unheated greenhouse. Soil penetration resistance was measured in situ next to each core location (0-80 cm depth, 1-cm resolution). We tested the number and species richness of seedlings observed in the soil segments (N= 320), using negative binomial generalized linear regression models, in which sampling layer and penetration resistance were the predictor variables. We ran the models for morphological groups (graminoids/forbs), ecological groups (grassland species/weeds) and life-form categories (short-lived/perennial). We also tested whether seed shape index, seed mass, water requirement or salt tolerance of the species influence the vertical distribution of their seed bank. Results: Germinable seed density and species richness in the seed bank decreased with increasing soil depth and penetration resistance. However, we detected nine How germinable seeds of six species even in the deepest soil layer. Forbs, grassland species and short-lived species occurred in large abundance in deep layers, from where graminoids, weeds and perennial species were missing. Round-shaped seeds were more abundant in deeper soil layers compared to elongated ones, but seed mass and ecological indicator values did not influence the vertical seed bank distribution. Our research draws attention to the potential ecological importance of the deeply buried seeds that may be a source of recovery after severe disturbance. As Vertisols cover 335 million hectares worldwide, these findings can be relevant for many regions and ecosystems globally. We highlight the need for similar studies in other soil and habitat types to test whether the presence of deep buried seeds is specific to soils with Vertic characteristics.
Keywords: Biológiai tudományok